Transgenerational impacts of oral probiotic administration in pregnant mice on offspring gut immune cells and colitis susceptibility. Issue 2 (21st November 2022) - Okada, Yoshikiyo; Sugihara, Nao; Nishii, Shin; Itoh, Suguru; Mizoguchi, Akinori; Tanemoto, Rina; Horiuchi, Kazuki; Tomioka, Akira; Nishimura, Hiroyuki; Higashiyama, Masaaki; Narimatsu, Kazuyuki; Kurihara, Chie; et al.
Abstract: Background and Aim: The study of the impact of environmental factors during pregnancy on fetal development has so far been focused primarily on those negatively affecting human health; however, little is known about the effects of probiotic treatment during pregnancy on inflammatory bowel diseases (IBD). In this study, we investigated whether oral administration of heat‐killed probiotics isolated from fermented foods decreased the vulnerability of offspring to IBD. Methods: Probiotics were administered to the pregnant mice until the birth of pups, after which the parent mice were maintained with autoclaved water. Partial pups were evaluated for dextran sodium sulfate‐induced colitis. The influence of CD11c + CD103 + dendritic cells (DCs) and regulatory T cells (Tregs) in mesenteric lymph nodes of parent mice and their pups was analyzed. Results: Oral administration of heat‐killed probiotics to pregnant dams significantly decreased inflammation induced by dextran sodium sulfate in pups. Probiotic treatment increased the number of CD103 + DCs, and the expression of β8‐integrin in CD103 + DCs and Tregs in mesenteric lymph nodes, not only in dams themselves but also in their offspring. Conclusions: Oral administration of probiotics during gestation induced transgenerational immunomodulatory effects on the gut‐associated immune system and resilience to experimental colitis in the offspring. Our results suggest that consumption of fermented foods during pregnancy can be effective in preventing inflammatory diseases such as IBD beyond generation.